Teaching literacies in diverse contexts (UCL PRESS, 2023)
Literacy education can take place in many locations and periods across the lifespan. Literacy educators require flexibility and a deep toolbox to meet their students' diverse needs, regardless of whether they work in traditional school and college settings or in other environments with varied populations. Teaching Literacy in Diverse Contexts shows how practical experiences can be used in creative ways to support educator development for teaching literacy in a global context.